The Impact of Economic Factors on Changing Carbon Emission Landscape in ASEAN With ARDL Approach - Hasbi, Hasbi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study aims to analyze the factors influencing carbon emissions in the member countries of the Association of Southeast Asian Nations (ASEAN). The data used in this study covers the period from 1990 to 2021, utilizing the Autoregressive Distributed Lag (ARDL) analysis method. All independent variables show a significant impact on carbon emissions in both the short and long term. This research provides evidence that factors such as urbanization, foreign direct investment, population, and economic growth significantly contribute to the increase in carbon emissions in ASEAN countries. The findings also validate the Environmental Kuznets Curve hypothesis for carbon emissions in ASEAN countries. In other words, economic growth leads to a reduction in carbon emissions. The ASEAN region has experienced substantial economic growth over the past few decades. However, carbon dioxide (CO2) remains a socio-economic issue in the ASEAN region. The results of this study can be highly beneficial for policymakers in the region regarding sustainability and economic development.